Experimental evaluation of thermal performance of cool pavement material using waste tiles in tropical climate - Anting N.; Md. Din M.F.; Iwao K.; Ponraj M.; Jungan K.; Yong L.Y.; Siang A.J.L.M. (Elsevier Ltd, 2023)
Aggregates; Coatings; Infrared devices; Pavements; Plating; Porcelain; Reflection; Surface properties; Experimental evaluation; Potential measurements; Solar reflectance; Spectral performance; Surface temperatures; Thermal Performance; Urban heat island; Urban Heat Island Effects; Atmospheric temperature